Dary autorskie dla Biblioteki Śląskiego Seminarium Duchownego w latach 1928-1939 (przyczynek do badań nad zawartością przedwojennego księgozbioru) - Olszowy, Ewa (Archiwa, Biblioteki i Muzea Kościelne, 2013)
The collections of the Library of Silesian Clerical Seminary, which history dates back to the 1920s, have not been examined satisfactorily to date. In the interwar period the library built its collections through purchases and generous donations. The article focuses on this part of donations which came from the authors themselves, mainly priests of Kraków archdiocese and Katowice diocese, secular persons in a minor extent. They donated 50 works in total, among them books, dissertations and articles previously published in periodicals. All of them were the latest publications on theology, Church history and related studies and covered a wide spectrum of religious issues. Some books are signed with author’s inscription, which greatly increases their value.